Impact assessment of electric vehicles on islands grids: A case study for Tenerife (Spain). (1st February 2017) - Colmenar-Santos, Antonio; Linares-Mena, Ana-Rosa; Borge-Diez, David; Quinto-Alemany, Carlos-Domingo
Abstract: The penetration of electric vehicles is a key instrument in the operation of smart grids. Their active participation in the electrical system is proposed as a tool to increase security of supply, successfully reducing the large differences that occur between periods of higher and lower electricity demand. This research presents an analysis of the vehicle-to-grid impact in low capacity electrical systems, as in the case of islands, aiming to establish a charge/discharge pattern that facilitates the penetration of electric vehicles in weak grids. In such a way, a comprehensive scenario needs to be assessed in order to obtain significant results to be applied not only in islands and outermost regions but also in scaled systems such as minigrids. To achieve this objective, a theoretical method for the efficient charge/discharge management of electric vehicles is proposed, defined by a multi-objective model based on criteria of mobility and technical requirements. The proposed model is applied to the island of Tenerife, which quantifies the electric vehicle penetration in a real case. The results show that grids in islands can assimilate "low" or "transition" penetrations of electric vehicles, so their use as storage systems allow to significantly reduce the amplitude difference between valleys and peaks of the electric energy demand curve and thereby to contribute to the efficient management of smart grids. Graphical abstract: Highlights: Multi-objective model based on actual criteria of mobility is proposed. The impact of charge-discharge patterns of EVs on energy demand curve is evaluated. Smart charge-discharge criteria is considered. Tenerife Island used as example for the analysis in low capacity electrical systems. Sensibility analysis is undertaken defining system behavior.